Can the lumbar-calibrated properties of the annulus fibrosus be extended to the thoracic level? Material model comparison. - Moreno-Vegas, Salvador; Peña Trabalón, Alejandro; Blanco-Salgado, Vicente; Estébanez-Campos, María Belén; Pérez-Blanca, Ana; Prado-Novoa, María (My University, 2025)
Two methodologies are distinguished for modeling the anisotropy of the annulus fibrosus (AF): axial springs simulating collagen fibers (CF) within hyperelastic ground substance (GS) layers; or the HGO material model to simulate CF and GS. Currently, both methodologies coexist but their advantages and disadvantages remain unclear. Lumbar AF properties have been calibrated via FEMs using experimental range of motion (ROM) data of functional spinal units and applied to lumbar and thoracic models, but thoracic validation is lacking. This study aims (i) to assess if the lumbar-calibrated material models can be extended to the thoracic segment and (ii) to compare the response of both methodologies with the experimental thoracic ROM.
Keywords: Biomecánica; Ingeniería biomédica; Vértebras - Propiedades mecánicas; Anillo fibroso; Modelo computacional; Modelo material; Extensibilidad